Image and Allegory: The Simulacral Logic of Piers's Pardon. (1st January 2013) - Asay, Timothy M
<x xml:space="preserve">Abstract</x> Poststructuralist readings of Piers Plowman have often centered on the semantic instability of its allegorical characters. The vision of a purely aesthetic world — in which all bodies are images circulating without final reference — offered by theorists of the simulacrum dramatizes most fully the poem's resistance to conservative, Platonic allegory. However, Langland curves this critique back on itself by suggesting that this aesthetic vision is likewise conceptual; art can never escape the syllogistic mode of allegory. The pardon scene brings these concerns into focus: Piers's pardon is a simulacrum that critiques his desire to be pardoned. Piers sought to exemplify only his ethic of honest labor, but his experiences with Waster and Hunger undermined it as an informing principle. The simulacral pardon, in which he hoped to find an apology justifying his labor, disabuses him of such identifying principles; however, Langland transforms this aesthetic disinvestment into the informing idea of his allegory, offering to Piers an iconic status that pervades all of the poem's characters.